Integrated Community-Based Conservation of Olive Ridley Sea Turtles in Response to Coastal Abrasion - Yudhi Ratna Nugraheni; Raden Wisnu Nurcahyo; Dwi Priyowidodo; Labib Abdillah; Artina Prastiwi; Vika Ichsania Ninditya; Edi Yulianto; Dhiannisa Ismoyo Putri (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Coastal abrasion and human activities have significantly degraded the nesting habitats of the olive ridley sea turtle (Lepidochelys olivacea). Purpose of the Study: This community service program aimed to save sea turtles through conservation activities, including nest relocation, hatching, and releasing hatchlings through a community-based collaborative approach. Methods: This community service focused on relocating olive ridley sea turtle nests threatened by coastal abrasion and developing hatching facilities. Through hatchling releases and conservation education, the program increased local community participation and promoted sustainable eco-tourism. Results: The program successfully relocated 28 nests containing 3,005 eggs, increasing hatching success from <50% to 64.7%. Monthly hatchling releases and educational activities increased community awareness and strengthened their role in eco-based sea turtle conservation